Problem-based learning to establish social presence: A mixed method investigation in different modes of classroom management practices - Murtafi'ah, Banatul; Ardini, Anandayu Suri (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
Post-pandemic learning has led schools in Indonesia to conduct a teaching transition from online to hybrid to offline learning. This uncertain situation has forced pre-service English teachers (PSETs), to be able to adapt to any mode of classrooms. Moreover, PSETs must have the social presence ability to manage online, offline, or hybrid classrooms. However, few studies examined how problem-based learning (PBL) can facilitate the establishment of social presence in classroom management practices among PSETs. This study investigates how PBL can establish PSETs"™ social presence. This convergent mixed-method study compares the social presence before and after the PBL implementation. Eighty PSETs joining the Language Classroom Management course completed a social presence questionnaire before and after the course. One open-ended question about their strategies to maintain students"™ engagement was added to the questionnaire. The result showed that the social presence score after the course (M=42.31) was significantly higher than before the course (M=40.80). It was also revealed that after the course, PSETs emphasized how teachers should also build relationships with students and ensure students"™ sense of belonging in the classroom. From these findings, the PSETs"™ social presence has been established through PBL implementation. While PBL supports teacher education and fosters social presence, further research should explore its integration.How to cite this paper: Murtafi"™ah, B. Ardini, A. S. (2024). Problem-based learning to establish social presence: A mixed method investigation in different modes of classroom management practices. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(1), 17"“34. http://dx.doi.org/10.26418/jeltim.v7i1.85447  There is no conflict of interest related to the publication of this article